Writing the Social : Critique, Theory, and Investigations - Smith, Dorothy E., 1926- (Book collections on Project MUSE., 1999)
"This collection of essays, written by Dorothy Smith over the past eight years, is a treasure by one of the world's foremost social thinkers. In it, Smith turns her wit and common sense on the prevailing discourses of sociology, political economy, philosophy, and popular culture, at the same time redefining her own sociological and feminist theory and practice."--Jacket.